2-Picoline catalyst-triggered [2 + 2 + 2] cycloaddition-type reaction of acetylenedicarboxylates, aldehydes and alkenes. Issue 33 (10th August 2018) - Tateishi, Keiichiro; Noguchi, Keiichi; Saito, Akio
Abstract : 2-Picoline efficiently catalyzes the formation of α, β-enones from acetylenedicarboxylates and aldehydes in the presence of alkenes, thereby leading to pyrans with complete regioselectivities. This method is represented as a first example of catalytic and metal-free [2 + 2 + 2] cycloaddition of three different components. Abstract : 2-Picoline efficiently catalyzes the formation of α, β-enones from acetylenedicarboxylates and aldehydes in the presence of alkenes, thereby leading to pyrans in moderate to good yields with complete regioselectivities. This synthetic method of pyrans is represented as a first example of catalytic and direct [2 + 2 + 2] cycloaddition of three different components under the metal-free conditions.